Change of micronucleus frequencies, antioxidant parameters and in silico in carp (Cyprinus carpio) fry exposed to ibuprofen - Kirici, Muammer; Tuzun, Burak; Yonar, Muhammet Enis; Poustforoosh, Alireza; Mise Yonar, Serpil; Seker, Engin; Ispir, Unal (Wiley, 2026)
Ibuprofen, a non-steroidal anti-inflammatory drug, has been detected in the aquatic environment, but little is known about its effects on fish and other aquatic organisms. This study aimed to investigate the effect of ibuprofen on micronucleus levels in erythrocytes and whole-body antioxidant parameters of carp (Cyprinus carpio) fry. Fish were exposed to immersion in two different doses of ibuprofen concentrations (50 and 250 mu g/L) for 24, 48, 72 and 96 h and 14 days. No mortalities occurred in any group during the test. Abnormal behaviours such as irregular swimming, loss of balance and hanging vertically in the water were observed in some fish exposed to acute toxicity. In this study, a significant increase in the micronucleus number of red blood cells was observed throughout the study period (p < 0.05). Antioxidant parameters were measured spectrophotometrically. Results obtained showed that ibuprofen significantly increased (p < 0.05) malondialdehyde (MDA) levels, glutathione S-transferase (GST) and catalase (CAT) activities, but decreased (p < 0.05) the glutathione (GSH) levels of whole-body carp fry in a dose-dependent manner. Furthermore, ibuprofen significantly increased MDA, GST and CAT levels, but increased the GSH levels of whole-body carp fry in a time-dependent manner. These results indicate that carp fry is sensible to human pharmaceutical agents in aquatic environments. The manner and the constructed interactions between ibuprofen and two protein targets (immunoglobin and haemoglobin) were investigated using molecular docking and molecular dynamics simulation. The results indicated that ibuprofen could affect the haemoglobin activity. Finally, absorption, distribution, metabolism, excretion and toxicity analysis was performed to examine the drug potential of the studied molecules.
Keywords: antioxidant system; Cyprinus carpio; ibuprofen; in silico; micronucleus